142 Human edible feed conversions of U.S. beef production. (5th December 2019) - Andreini, Emily M; Place, Sara E; Oltjen, James W
Abstract: Multiple factors need to be considered in assessing the sustainability of ruminant livestock production, such as the valuable role ruminants serve in the conversion of feeds grown on non-arable lands and by-products into products suitable for human consumption. The use of intensive systems, where ruminants are fed large quantities of potentially human edible crops, such as cereal grains, poses a debate about the competition between livestock and humans for grains that could be consumed directly by humans. The inclusion of animal products in human diets provides an important source of energy and protein, which often have higher digestibility and superior amino acid compositions. This analysis was conducted for seven U.S. regions in order to determine the human edible feed conversion efficiency (heFCE) of energy and protein and the net protein contribution (NPC) of U.S. beef production using data collected by the National Cattlemen's Beef Association. Efficiency and NPC values above 1 indicate that beef production is contributing more to meeting human protein or energy requirements than the cattle are consuming, and values below 1 indicate beef is competing for those nutrients. The Southwest and Southeast regions returned heFCE values for energy above 1, while the average of all regions was 0.88 ± 0.27 SD. All regions had heFCE values for protein above 1 with an average of 1.73 ± 0.54 SD. The NPC of all US regions were greater than 3; averaging 4.55 ± 1.41 SD, which illustrates beef's contribution of high quality protein to human diets. Incorporating a detailed evaluation of different production system efficiencies in converting potentially human edible feeds into human edible animal products of higher quality broadens the discussion for beef's place in the diet.